Dance as an agency of change in an age of totalitarianism - Hellsten, Laura (Approaching Religion, 2022)
This article identifies two different paths where the amnesia described by Hannah- Arendt and the fragmentation identified by Willie James Jennings of our historical past has distorted how people today view dan-cing. I set out how the Christian entanglement with colonial powers has impacted on people’s abilities to relate to their bodies, lands and other creatures of the world. I describe how the colonial wound of Western society forms the basis of the loneliness and alienation that totalitarianism inculcates. After this, I examine how people who seek to find a solid tradition of dance within the Western traditions of Christianity often end up in a conundrum when they seek to legitimize the existence of the tradition in the wrong places. I show how seeking roots for Christian dance practices in Jewish customs is often entangled in supersessionist understandings. These arguments are constructed by means of both J. Kameron- Carter’s writings on race and theology and the black political theology outlined by Vincent W. Lloyd. The second-most-often chosen option for creating a dance tradition for Western forms of Christianity is to romanticize the non-Western ‘other’. Using Lindsey Drury’s work, I argue that dancers have perpetuated the interests that seek to possess the ‘other’ by bringing exotic dancers to the Western marketplace. Finally, I describe the third option – more commonly found amongst those critical of Christian tradition – to seek the roots of transformational dance practices in Hellenistic and more esoteric teachings flourishing in the early twentieth century. We run into the often forgotten or neglected stories of renowned dance teachers like Rudolf Laban and Isadora Duncan on this path. By combining esoteric bodily practices, Mother Earth ‘spirituality’ and superior views about race, they not only promoted but laid the foundation for how people were manipulated in the Third Reich. I end by sharing ethnographic stories of resistance towards how these past historical patterns have affected how dance is viewed today. Those exhibiting such resistance are not always consciously aware of the historical roots I have described. However, engagement in contemplative and healing dance practices seems to be forging new and better ways to create community and to live in a connected way with creation and our creatureliness (Hellsten 2021a). The central theme of these practices is to resist the illusion of perfection and control while helping people to listen to and discern the Holy Spirit leading them into a new way of living.